2019
DOI: 10.3747/pdi.2018.00193
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis Cuff-Shaving—A Salvage Therapy for Refractory Exit-Site Infections

Abstract: Introduction Cuff-shaving has been described as a salvage technique for refractory exit-site infections, with conflicting data regarding infection and catheter outcomes. We describe our experience with cuff-shaving as a rescue therapy for exit-site infections unresponsive to systemic therapy. Methods We retrospectively reviewed patients who underwent cuff-shaving between January 2012 and June 2017. Refractory exit-site infection was defined as purulent discharge from the exit site with no clinical response aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
0
9
0
4
Order By: Relevance
“…This may suggest another source of the gramnegative peritonitis, such as bowel or touch contamination. Regardless of the bacteriologic cause, the presence of ESI was associated with a lower complete cure rate but not primary response rate in gram-negative peritonitis [40]. Approximately 2.8% of Enterococcus faecalis ESI and 12.8% of Serratia ESI were associated with catheter loss [9,41].…”
Section: Other Gram Negative Organismsmentioning
confidence: 94%
See 1 more Smart Citation
“…This may suggest another source of the gramnegative peritonitis, such as bowel or touch contamination. Regardless of the bacteriologic cause, the presence of ESI was associated with a lower complete cure rate but not primary response rate in gram-negative peritonitis [40]. Approximately 2.8% of Enterococcus faecalis ESI and 12.8% of Serratia ESI were associated with catheter loss [9,41].…”
Section: Other Gram Negative Organismsmentioning
confidence: 94%
“…If no improvement is seen after 3 weeks of antibiotic therapy for any ESI, the infection is considered a refractory ESI [40]. Catheter replacement or removal is often considered for refractory ESI.…”
Section: General Principlesmentioning
confidence: 99%
“…Additionally, prior reports have shown that M. abscessus ESI/TI can spread through the para-catheter route to cause peritonitis [20]. Together, these results suggest that while surgical interventions such as cuff shaving, deroofing, and SCRR may have promising outcomes in PD technique survival in otherwise uncomplicated ESI, these approaches appear inappropriate for M. abscessus ESI/TI [4,5,21].…”
Section: Discussionmentioning
confidence: 86%
“…No literature to date describes extrusion of the deep cuff in a still functional PD catheter. Extrusion of the superficial catheter cuff may require interventions such as cuff-shaving to increase the longevity of PD catheters and reduce the need for replacement of such catheters and prevent catheter-related infections [ 3 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%